Occupational limbo, transitional liminality, and permanent liminality: new conceptual distinctions - Bamber, Matthew; Allen-Collinson, Jacquelyn; McCormack, John (SAGE, 2017)
This article contributes new theoretical perspectives and empirical findings to the conceptualization of occupational liminality. Here, we posit ‘occupational limbo’ as a state distinct from both transitional and permanent liminality; an important analytic distinction in better understanding occupational experiences. In its anthropological sense, liminality refers to a state of being betwixt and between; it is temporary and transitional. Permanent liminality refers to a state of being neither-this-nor-that, or both-this-and-that. We extend this framework in proposing a conceptualization of occupational limbo as always-this-and-never-that, where this is less desirable than that. Based on interviews with 51 teaching-only staff at 20 research-intensive ‘Russell Group’ universities in the United Kingdom, the findings highlight some challenging occupational experiences. Interviewees reported feeling ‘locked-in’ to an uncomfortable state by a set of structural and social barriers often perceived as insurmountable. Teaching-only staff were found to engage in negative and often self-depreciatory identity talk that highlighted a felt inability to cross the līmen to the elevated status of ‘proper academics’. The research findings and the new conceptual framework provide analytic insights with wider application to other occupational spheres, and can thus enhance the understanding not just of teaching-only staff and academics, but also of other workers and managers.
Keywords: Academic careers; liminality; limbo organisational theory; work environment